Treatment of Clostridium difficile infection in mice with vancomycin alone is as effective as treatment with vancomycin and metronidazole in combination. Issue 1 (31st December 2015) - Erikstrup, Lise Tornvig; Aarup, Mie; Hagemann-Madsen, Rikke; Dagnaes-Hansen, Frederik; Kristensen, Brian; Olsen, Katharina Elisabeth Pribil; Fuursted, Kurt
Abstract : Objective: Clostridium difficile is a major cause of nosocomial infectious diarrhoea. Treatment of C. difficile infection (CDI) depends on disease severity. A combination of vancomycin and metronidazole is often recommended in severe cases. The aim of this study was to examine, in a murine model of CDI, if mice treated with a combination of vancomycin and metronidazole had a better clinical outcome than mice treated with vancomycin or metronidazole alone. Design: C57BL/6J mice pretreated with an antimicrobial mixture were challenged with C. difficile VPI 10463 or phosphate-buffered saline by oral gavage. After the challenge, the mice were treated with placebo, vancomycin, metronidazole or a combination of vancomycin and metronidazole for 10 days. The mice were monitored for 20 days with weight and a clinical score. Stool samples were examined for C. difficile spore load and presence of C. difficile toxins. Results: None of the mice in the vancomycin-treated group died during the treatment phase compared to a mortality of 17%, 33% and 55% in the combination, metronidazole and infected control group, respectively. Mice treated with vancomycin alone or in combination with metronidazole recovered from CDI faster than mice treated with metronidazole alone. However, after discontinuation of treatment, vancomycin-treated and combination-treated mice succumbed to clinical and bacteriological relapse. Conclusions: Mice treated with vancomycin alone had a better clinical outcome in the treatment phase of CDI than mice treated with metronidazole alone. A combination of vancomycin and metronidazole did not improve the clinical outcome when compared to treatment with vancomycin alone. Trial registration number: The trial registration number from the Danish Experimental Animal Inspectorate is J number 2012-15-2934-00422.